Multiple Nutrient Stresses Accentuating Citrus Decline in Northeast India - Srivastava, A K (Indian Horticulture, 2024)
Khasi mandarin (Mostly seedling origin with extended juvenile period) is one of the commercial citrus cultivars grown predominantly in rainfed and naturally organic environment, with minimum use of synthetic inputs. Under such nutritionally compromised conditions, identifying the correct nutritional disorders and resort to an effective remediation surmount to quite a challenging task. The extensive research has developed nutrient diagnostics (using leaf nutrient guide and soil fertility rating coupled with morphological descriptors) to identify multiple nutrient stresses (Ca, Mg , Zn, N, P and B in decreasing order) playing an interlocuter in citrus decline rampant deep in northeast India. These nutrient stresses need to be addressed using different protocols of organic cultivation and integrated nutrient management as suggested. The efforts such as these must complement in-situ rainwater conservation as a part of contingency irrigation to contain the current onslaught of citrus decline in Northeast India.